Review - Disruptive Innovation and Information Technology – Charting a path. - Abayomi Baiyere; Hannu Salmela (Melbourne Australia, 2022)
While it has been established that the Information technology (IT) capability of an organization contributes to its ability to innovate and respond to threats, very little has been done in understanding the significance, if any, of the role of IT in disruptive innovation (DI) scenarios. This paper systematically reviews prior research on the concept of DI in relation to IT. Importantly, this paper lays out a research agenda for the exploration of IT and IS research on the subject of DI. Topical questions are raised and calls are made for further studies to position the relevance of IT/IS to the maturing discussion of disruptive innovation. Concurrently, a general review of the evolution of the theory of disruptive innovation and its current status is also presented. A framework classifying disruptive innovation based on typology and definitions is demonstrated in tandem with ensuing questions on the role of information technology.
Australasian Conference on Information Systems